Mechanisms of H2pmen-Induced cell death: Necroptosis and apoptosis in MDA cells, necrosis in MCF7 cells - Nosipho Ntanzi; Rene B. Khan; Mthokozisi B. Nxumalo; Hezekiel M. Kumalo (Heliyon)
Breast cancer is the second leading cause of cancer-related deaths in women around the world. Several cancer therapeutics have already been discovered and are being used to treat breast cancer. However, most of them cause severe side effects. H2pmen, a tetradentate ligand, was used in this study to investigate its cytotoxic effects on growth, viability, and induction of cell death in MCF7 and MDA cells. The cell viability was determined by treating cells with different concentrations of H2pmen. MTT assay was used to obtain an IC50, and the cells were then assayed for membrane damage, apoptotic induction, and metabolism. Protein expression of Bax, p53, Bcl2, and xIAP was identified using Western blot analysis. The gene expression of RIPK1, RIPK3, and MKLK was determined using qPCR. In MDA cells, H2pmen increases cytotoxicity, as evidenced by upregulated LDH and JC-10, and enhances apoptosis, indicated by upregulated caspase-3/7 and Bax. In contrast, MCF7 cells exhibit a more stable profile with downregulated LDH and Annexin V Activity. MCF7 cells also show reduced necroptosis and increased necrosis. These findings highlight that H2pmen induces varied cytotoxic effects across MDA and MCF7 cells, with MDA cells exhibiting more pronounced apoptosis and necroptosis alongside complex anti-apoptotic responses.